The issue of the environmental anthropology depicted by Patrycja K. Townsend - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2005)
Environmental anthropology is a much wider term than ecology itself because of its extensive and diverse issues. The environmental questions appeared significantly in anthropology in the 1950 s with the Julian Stewards cultural ecology. Later Andrew Vayda and Roy Rappaport suggested the term known as ecosystem ecology. From the late 1970s, evolutionary ecology has become more popular. The other attempts to the issues of the natural environment within the confines of anthropology are ethnoecology, historic ecology, global ecology, and landscape ecology. The article presents environmental anthropology depicted by P. K. Townsed.